USING THE ENGLISH LANGUAGE FOR PRACTICAL PURPOSES - M. M. Artikova (International Engineering Journal For Research & Development, 2020)
This article deals with how to interact with colleges, read instructions, write memos, handle telephone calls, welcome, guests or customers and etc., in order to use the language for practical purposes